2002
DOI: 10.1021/cm010375z
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Properties of Photonic Films from Polymer Beads by Chemistry

Abstract: This paper describes the preparation of monodisperse colloids from various methacrylates. These colloids sediment well on glass slides and formsin the dried stateslarge threedimensional face-centered cubic photonic crystal films with Bragg reflection in the visible region. Depending on crystallization conditions, the domain sizes vary between 50 and 300 µm. By cross-linking the polymer within the colloids, it is possible to increase the thermal stability of the polymeric photonic structure tremendously (up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 30 publications
1
88
0
Order By: Relevance
“…Number of pioneering literatures have reported that the polymeric microspheres having the diameters in the range of 100 ~ 400 nm fall in such "photonic grade" microspheres. 14,16,[24][25]27 We have confirmed that the polymer microspheres from the acrylic monomer such as MMA, tBMA within the size of photonic grade could be conveniently synthesized without the use of surfactant which usually takes part in the emulsion polymerization. 24 In SFEP, the initiation takes place by scission of potassium persulfate, followed by radical attacks to some monomers to form charged oligomers.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Number of pioneering literatures have reported that the polymeric microspheres having the diameters in the range of 100 ~ 400 nm fall in such "photonic grade" microspheres. 14,16,[24][25]27 We have confirmed that the polymer microspheres from the acrylic monomer such as MMA, tBMA within the size of photonic grade could be conveniently synthesized without the use of surfactant which usually takes part in the emulsion polymerization. 24 In SFEP, the initiation takes place by scission of potassium persulfate, followed by radical attacks to some monomers to form charged oligomers.…”
Section: Resultsmentioning
confidence: 94%
“…14,16,[24][25]27 We have confirmed that the polymer microspheres from the acrylic monomer such as MMA, tBMA within the size of photonic grade could be conveniently synthesized without the use of surfactant which usually takes part in the emulsion polymerization. 24 In SFEP, the initiation takes place by scission of potassium persulfate, followed by radical attacks to some monomers to form charged oligomers. Such oligomers behave as surfactants to stabilize monomer droplet (micelle), resulting in the growth of polymer microsphere in a similar manner as "classical" emulsion polymerization.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations